European Development Fund - Commission of the European Communities (Brussels : The Directorate-General, 1974)
This document deals in the management of financial and technical cooperation between the European Economic Community and the Associated States (AASM) during 1973, the third year of application of the second Yaunde Convention
osc 21/11/2018
Loans
Keywords: Economic assistance, European; Technical assistance, European